Awareness: A Strategic Tool for The Implementation of Green Libraries by Academic Librarians - Emmanuel, Helen; Okojie, Victoria (Ghana Library Journal, 2022)
This study sought to examine the importance of awareness in the adoption and implementation of green libraries in academic libraries in Nigeria. The key objectives were to determine academic librarians’ awareness of the concept of green libraries, ascertain if greening libraries is a good innovation for adoption and implementation, ascertain reasons for the slow adoption and implementation of green libraries by academic librarians in Nigeria and to identify strategies for enhancing green library implementation in Nigerian academic libraries. The methodology used was the descriptive survey research design while all the 170 academic librarians in the twelve university libraries across the six states of the North Central geo-political zone of Nigeria and the Federal Capital Territory, Abuja formed the population of the study. Questionnaire was used as the instrument for data collection. Data obtained were analyzed using simple percentages, mean scores and standard deviation. Various suggestions were made on how to create awareness and use it as a strategic tool in the implementation of green libraries in academic libraries. The paper concluded that implementing green libraries will enhance the visibility and value of libraries in society by showcasing their ability to contribute significantly to environmental sustainability and development issues, thereby demonstrating their continued relevance to humanity.